(untitled) (Plant Tissue Culture and Biotechnology, 2015)
KNOTED1-LIKE from Arabidopsis thaliana (KNAT1) gene keeps shoot apical meristem (SAM) in the meristematic state. The objective of the research was to investigate whether the function of KNAT1 gene in keeping plant cells under meristematic state was functionally still work in the organ of the KNAT1 transformant. The transformant and WT plants were micropropagated, sliced and cut into some pieces, i.e. base of root, middle of root, root tip, a whole shoot, base of leaf, and leaf tip and planted in the New Phalaenopsis medium added with and without 5μM 2-iP and 0.15 μM NAA. The results show that cells of KNAT1 transformant were more meristematic compared to wild type plants as the organ produced more buds in micropropagation. Plant Tissue Cult. & Biotech. 25(1): 13-20, 2015 (June)